Design of a Two-channel Instrument to Record Lung and Heart Sounds Simultaneously and Separate Them Using ANC-NLMS Algorithm - Al-Naggar, Noman Qaid; Ghazi, Hamdi H. (International Journal of Advanced Research in Electrical, Electronics and Instrumentation Engineering, 2015)
An effective lung sound (LS) recording instrument plays a major role in the diagnostic field because it can extract many types of information, such as symptoms or markers, to achieve various LS pathologies. This study proposes to develop a two-channel instrument (electronic stethoscope) for recording heart sound (HS), reference signal, and original signal (which includes LS and HS) simultaneously from the same subject. These recorded signals provide input requirements of adaptive noise cancellation (ANC) filter used for separating the original signal (LS+HS) and reference signal (HS). Normalized least mean square (NLMS) algorithm is applied to operate efficiently with two signals recorded at the same time because its computation is faster than that of LMS algorithm. A two-channel instrument is subjected to the specific requirements of heart and lung sounds, particularly in sensors and pre-amplification and filtering. Consequently, the designed instrument and ANCNLMS algorithm demonstrated corresponding observed on uniformity and components (peaks, phases, and time delay) of original and reference signals before and after separating HS. The obtained pure LS signal maintained its uniformity and time delay. In addition, the performance of the proposed method is verified using power spectral density (PSD) of signals, as follows: the original (LS+HS), separated HS, reference HS, and obtained pure LS before and after separation. The PSD showed the difference of these signals in terms of average power and different frequency ranges of LS pathology. The designed instrument and ANCNLMS algorithm obtained efficient and satisfactory results in separating LS and HS. The analysis process was implemented and displayed in Matlab platform.